2011
DOI: 10.1088/0253-6102/56/3/11
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Friedmann Equation of FRW Universe in Deformed Hořava—Lifshitz Gravity from Entropic Force

Abstract: With entropic interpretation of gravity proposed by Verlinde, we obtain the Friedmann equation of the Friedmann-Robertson-Walker universe for the deformed Hořava-Lifshitz gravity. It is shown that, when the parameter of Hořava-Lifshitz gravity ω → ∞, the modified Friedmann equation will go back to the one in Einstein gravity. This results may imply that the entropic interpretation of gravity is effective for the deformed Hořava-Lifshitz gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…The entropic interpretation of gravity has been used to extract Friedmann equations at the apparent horizon of the Friedmann-Robertson-Walker universe [34,35], modified Friedmann equations [36,37], modified Newton's law [38], the Newtonian gravity in loop quantum gravity [39], the holographic dark energy [40][41][42], thermodynamics of black holes [43] and the extension to Coulomb force [44]. Other studies on the entropic force have been carried out in [45][46][47][48][49][50][51][52][53][54].…”
mentioning
confidence: 99%
“…The entropic interpretation of gravity has been used to extract Friedmann equations at the apparent horizon of the Friedmann-Robertson-Walker universe [34,35], modified Friedmann equations [36,37], modified Newton's law [38], the Newtonian gravity in loop quantum gravity [39], the holographic dark energy [40][41][42], thermodynamics of black holes [43] and the extension to Coulomb force [44]. Other studies on the entropic force have been carried out in [45][46][47][48][49][50][51][52][53][54].…”
mentioning
confidence: 99%
“…In [7], it is shown that the holographic dark energy will be derivable from the entropic force interpretation of gravity. The modified Friedmann equations by this notion of gravity are obtained in different setups such as Einstein gravity [8], braneworld scenarios [9], Gauss-Bonnet gravity [10], and Hořava-Lifshitz gravity [11]. There are also other applications of Verlinde's hypothesis, some of which are mentioned in [12].…”
Section: Introductionmentioning
confidence: 99%
“…28 This hypothesis is generalized to various theories of gravity and cosmological setups. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Therefore, the tendency of the cosmos, as a closed system, to increase its entropy is compatible with the current accelerated phase of the expansion. Finally, we should note that the thermodynamic analysis of the universe helps us to get a better understanding from the gravity, the universe, its origin and evolution, and thus the nature of the mysterious dominated fluid supporting the current accelerated expansion.…”
Section: Introductionmentioning
confidence: 99%